(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Elimination of pain is one of the most important duties of a doctor. A surgeon has to come across more number of cases where management of pain becomes a handful. Thus proper use of analgesics both systemic and local are an integral part of any successful surgery. For decades NSAIDs has been the go to drug for management of pain and administering anaelgesia. But recent pharmacological advancements have opened up a new way of administering anaelgesia in the form of synthetic opiods. This review article aims at finding out the efficacy of local administration of TRAMADOL in maxillofacial surgeries.